The use of improvised chemicals and materials in teaching and learning chemistry in two selected districts of Rwanda - Celestin Ngendabanga; Jean Baptiste Nkurunziza; Leon Rugema Mugabo (Cogent Education)
This study investigates the teaching practices of chemistry teachers in two selected districts of Rwanda, focusing on their use of improvised chemicals and materials in resource-constrained settings. Employing a qualitative phenomenological design, data were collected through interviews, classroom observations, and document analysis from eight experienced chemistry teachers. The study explores how teachers deliver chemistry concepts, the challenges they face in conducting practical sessions, and the effectiveness of improvised materials in enhancing student learning. Findings reveal that while theoretical teaching dominates due to material shortages, improvised chemicals like ash, lemon, and eggshells are occasionally used to bridge the gap between theory and practice. However, limited resources, large class sizes, and insufficient training hinder the full integration of practical sessions. The study highlights the potential of improvised chemicals and materials to improve student engagement and understanding of complex concepts. Recommendations include targeted teacher training and resource support to enhance chemistry education in resource-limited schools.